Revitalization of Cultural Tourism Destinations for the Outside of Uluwatu Temple in the New Normal Era - I Made Wijaya Kusuma; I Wayan Winaja; I Wayan Budi Utama (International Journal of Interreligious and Intercultural Studies, 2022)
The outbreak of the Covid-19 pandemic at the beginning of 2020 in Indonesia and around the world made Bali tourism really experience an extraordinary downturn. To the extent that Bali's economy has fallen far below the national economic growth, which previously surpassed national economic growth, reaching more than 5% (Bank Indonesia Bali Report May 2020). Especially for Bali, it is necessary to immediately address all affected tourist destinations. The quick and appropriate steps to restore Bali's tourism conditions are through the recovery of post-Covid-19 Bali tourism, known as the revitalization of tourist destinations. This study focuses on (1) the factors causing the revitalization of cultural tourism destinations outside the Uluwatu temple in the new normal era, (2) the process of revitalizing cultural tourism destinations outside the Uluwatu temple in the new normal era, (3) the implications of revitalizing tourist destinations the culture of the area outside the Uluwatu temple on socio-cultural, economic, and religious life in the new normal era. The theory used in this research is; (1) Reconstruction theory put forward by George S. Count and Harold Rugg which says society needs reconstruction/change and social change involves changing education, using education in changing society; (2) Structural Theory by Anthony Giddens which says individuals are agents who have a lot of knowledge (knowledgeable agents) and the ability to understand their own actions; and (3) Stuart Hall's Reception Theory which says that audience members can play an active role in decoding messages because they depend on their own social context, and may be able to change the message themselves through collective action, which means the community's response to the implementation of revitalization. cultural tourism destinations outside the Uluwatu temple. This research uses qualitative analysis method with interpretive descriptive. The results obtained are as follows; (1) the revitalization program is very much in line with the trend of government programs after the Covid-19 outbreak, which is highly expected by tourists today because of the implementation of CHSE-based health protocols (Cleanliness, Healthy, Safety, Environment) in the new normal era regarding the revitalization of tourist destinations; (2) the process of revitalizing tourist destinations in the new normal era, there are 3 strategies applied to accelerate the revitalization, namely; a) Innovation, b) Collaboration, c) Communication; (3) the implications of revitalizing cultural tourism destinations outside the Uluwatu Temple in the new normal era, namely the socio-cultural life of the community is stretching again, the economy is starting to grow and religious behavior in the aspect of the dimension of belief makes people closer to Ida Shang Hyang Widi Wasa.